Configurações das infâncias na constituição de personagens crianças em obras de Literatura Infantojuvenil Indígena Brasileira - Santos, Márcia Dias dos (2024)
For more than five hundred years, indigenous peoples have shown themselves to be great warriors revealing countless ways to resist attacks on their own existences. In current times, one of the forms of movement that evokes a systematized organization is the occupation of indigenous men and women in literary spaces, as agents in writing processes. These writers, today, with a considerable number of published books, have presented to the reading public numerous literary works that demarcate a territory of belonging to the universe of literary language and become a guiding thread, whose elements reveal the culture, history, and indigenous imaginary, intrinsically linked between orality and writing. Moreover, this literature is configured as a great ally in the search for visibility of indigenous peoples and the valorization of their stories. Among these various productions, for this Thesis, we chose to highlight indigenous literature aimed but not limited to the youth audience. The Thesis aims to analyze the configuration of childhood in the constitution of child characters in Brazilian indigenous children's literature, aiming to understand the relationship of childhood as a literary aesthetic project that provides an experience of writing and reading articulated by the complex links of the historical-cultural figurations of a non-hegemonic society and that is configured as a possible area of traces and reconstitutions of the memory of indigenous peoples. Thus, we seek dialogues, especially with indigenous authors to discuss issues about indigenous literature, children, and indigenous childhood, as well as we scrutinize the relationship between child characters and children's literature. To this end, this study presents the analysis of childhood in two works by Eliane Potiguara and in two works by Yaguarê Yamã. Finally, the results point to multiple childhoods, constituted by child characters, which promote connections between ideas of being an indigenous "child," linked to knowledge and practices, whose times, spaces, and social relations aim to detach from the homogeneous and distorted idea of the indigenous childhood universe, constructed through the lens of the subalternization of the other that was composed in/by literature.